2012
DOI: 10.1007/s12289-012-1092-9
|View full text |Cite
|
Sign up to set email alerts
|

The optimal die semi-angle concept in wire drawing, examined using automatic optimization techniques

Abstract: International audienceCoupling of evolutionary algorithms (EA) with meta-models (MM) is used to investigate the concept of the optimal die semi-angle in wire drawing. Traditional process design by minimization of the wire drawing force highlights an optimal die angle which increases with friction factor and reduction ratio. When wire drawing optimization is applied on the Latham and Cockcroft damage criterion, an optimal die semi-angle no longer appears: in this mono-objective optimization, the lowest industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Although successful applications were obtained with above-mentioned studies, few of these results were validated by experiments. Massé et al (2013) performed an optimization on a single drawing pass to deduce an optimal die angle to minimize drawing force and damage using the Latham-Cockcroft fracture criterion (Cockcroft and Latham, 1968). Based on multi-objective optimization, the authors showed that for the range of industrially used angles, a strong decrease of damage could be obtained at the expense of small increase of drawing force.…”
Section: Introductionmentioning
confidence: 99%
“…Although successful applications were obtained with above-mentioned studies, few of these results were validated by experiments. Massé et al (2013) performed an optimization on a single drawing pass to deduce an optimal die angle to minimize drawing force and damage using the Latham-Cockcroft fracture criterion (Cockcroft and Latham, 1968). Based on multi-objective optimization, the authors showed that for the range of industrially used angles, a strong decrease of damage could be obtained at the expense of small increase of drawing force.…”
Section: Introductionmentioning
confidence: 99%
“…Die angle is important parameter in wire drawing process since it strongly affects homogeneity of mechanical properties of drawn wire along the radial direction as well as drawing force. [18][19][20] Figure 4 shows the deformation behaviors of surface flaw of drawn wire with die angle and total RA. The depth of surface flaw decreased with increasing total RA, but the deformed shape of surface flaw was different with die angle.…”
Section: Die Anglementioning
confidence: 99%
“…Although the properties of the drawn wire have complex interactions with several process parameters, three process parameters in particular can affect the abovementioned four issues during wire drawing: reduction of area (RA) per pass, die angle, and friction at the wire-die interface. Therefore, many researchers have investigated the influence of RA per pass [6,12,13], die angle [14][15][16], and friction at the wire-die interface [17,18] on the drawing force, strain inhomogeneity, defects, and die life.…”
Section: Introductionmentioning
confidence: 99%